Human development, unemployment and Indonesian migrant workers / Fariastuti Djafar - Djafar, Fariastuti (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
This paper focuses on three objectives. The first objective is to examine the long-run relationship among human development, unemployment and the Indonesian Migrant Workers (IMWs). This is followed by examining the causality between the human development and unemployment, respectively, and the IMWs in the second objective. The effect of human development and unemployment on the IMWs is examined in the third objective. The study is based on time series data and utilizes a Vector Autoregressive (VAR) framework. The findings show that human development, unemployment and the IMWs are cointegrated. Human development and unemployment, respectively, causes the IMWs in the short- and long-run. Human development has a negative significant effect on the IMWs while unemployment has a positive significant effect on the IMWs.